Materials that harness and modulate the immune system. (10th January 2014) - Lewis, Jamal S.; Roy, Krishnendu; Keselowsky, Benjamin G.
Abstract: Abstract : Recently, biomaterial scientists have married materials engineering and immunobiology to conceptualize new immunomodulatory materials. This special class of biomaterials can modulate and harness the innate properties of immune functionality for enhanced therapeutic efficacy. Generally, two fundamental strategies are followed in the design of immunomodulatory biomaterials: (1) immuno-evasive (immuno-mimetic, immuno-suppressing, or immuno-inert) biomaterials and (2) immuno-activating or immuno-enhancing biomaterials. This article highlights the development and application of a number of immunomodulatory materials, categorized by these two general approaches.